Association of the functional polymorphism in the catechol-O-methyltransferase gene with schizophrenia in the three ethnic groups of the Malaysian population - Wan, C.L.; Zainal, N.Z.; Lian, L.H.; Mohamed, Z. (2011)
The catechol-O-methyltransferase (COMT) gene is a candidate gene for schizophrenia as its encoded enzyme is involved in the metabolic inactivation of dopamine and noradrenaline. Several molecular genetic studies thus far have demonstrated that the COMT functional polymorphism of Val158Met is susceptible with schizophrenia. Hence, the present study aims to determine this genetic association of this SNP in the three major ethnic groups of the Malaysian population. A total of 317 patients (79 Malays, 154 Chinese and 84 Indians) meeting DSM-IV criteria for schizophrenia and 417 healthy subjects (160 Malays, 164 Chinese and 93 Indians) were recruited. A PCR-RFLP method was used to determine the genotypes and alleles present. We found a significant association of genotypes within the total pooled samples, as well as in the female subgroup, with a higher frequency of heterozygotes in schizophrenia subjects. However, there were no significant differences in allele and genotype frequency between the schizophrenic patients and normal controls in all three ethnic groups. Our current findings suggest that the Val158Met polymorphism has a weak association with schizophrenia in the Malaysian population and does not play a major role in conferring susceptibility to the schizophrenia in any of the three major local ethnicities. Â© 2011 Elsevier Ltd.